Kesediaan Membayar Pengguna terhadap Peningkatan Kualitas Layanan Commuter Line - Philip, Fredy Jhon; Fassa, Ferdinand; Nurhidayah, Fitriyah (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2018)
The purpose of the research is to find out the relations between Commuter Line passengersâ characteristics and factors affect respondentsâ answers of Willingness to Pay (WTP). Since October 2017, PT. KAI has operated Commuter Line from Cikarang to Jakarta Kota to enhance the mobility of Cikarang residents and the surrounding areas. The operational activity of Commuter Line should consider the consumers ability in paying and the quality of services provided by the operators. The data was collected by spreading the questioners to passengers in Cikarang station. The data was analyzed using quantitative descriptive and tabulated using SPSS. There are six characteristics with sufficient results related to passengersâ satisfactory in using Commuter Line which are reliability, comfort, safety, easy access, equality, and secure. Factors affect WTP are income and purpose of the travel. The result shows that WTP is Rp.9.796 which means increasing about 95 % if the quality of services is also increasing